2007
DOI: 10.1016/j.neuron.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 Enhances Depolarization-Induced GABA Release

Abstract: Neuregulin-1 (NRG1), a regulator of neural development, has been shown to regulate neurotransmission at excitatory synapses. Although ErbB4, a key NRG1 receptor, is expressed in glutamic acid decarboxylase (GAD)-positive neurons, little is known about its role in GABAergic transmission. We show that ErbB4 is localized at GABAergic terminals of the prefrontal cortex. Our data indicate a role of NRG1, both endogenous and exogenous, in regulation of GABAergic transmission. This effect was blocked by inhibition or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
317
1
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(335 citation statements)
references
References 51 publications
16
317
1
1
Order By: Relevance
“…We focused on the processing of Nrg1 and its receptor ErbB4 because the link between Nrg1, cognition, and the pathogenesis of schizophrenia has been made (12)(13)(14)(15). We cannot exclude the contribution of deficient processing of other substrates such as N-cadherin (data not shown) or amyloid precursor protein (6) to the phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on the processing of Nrg1 and its receptor ErbB4 because the link between Nrg1, cognition, and the pathogenesis of schizophrenia has been made (12)(13)(14)(15). We cannot exclude the contribution of deficient processing of other substrates such as N-cadherin (data not shown) or amyloid precursor protein (6) to the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Nrg1 signaling via its receptor ErbB4 regulates NMDA receptor function of GABAergic interneurons in the PFC (10,12,13), and this regulation is perturbed in schizophrenic patients (14). Nrg1 signaling also regulates GABA release by these interneurons (15) and modifies their levels of ␣7 nicotinic acetyl choline receptors (16). How Nrg1 is mechanistically involved in the pathogenesis of schizophrenia remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we used an ErbB4 inhibitor, AG1478, which prevents ErbB4 signaling 45,46 . We found that bath-applied AG1478 prevented NRG1β-mediated suppression of the Src enhancement of synaptic NMDAR currents (Fig.…”
Section: Nrg1β-erbb4 Blocks Src Enhancement Of Nmdar Epscs In Ca1mentioning
confidence: 99%
“…In agreement with this, NRG-1 has been shown to stimulate GABA release. 21 Interestingly, hypofunction of GABAergic interneurons, in particular of cells that express parvalbumin (PV), has been suggested to contribute to the etiology of schizophrenia. [22][23][24][25] Basket and chandelier cells that provide powerful perisomatic inhibition control and time the population firing of principal glutamatergic neurons, thereby coordinating network activity.…”
Section: Location Location Locationmentioning
confidence: 99%